echanism at Antibacterial Activity of Lb. plantarum kik Metabolites and Monoacylglycerol Coconut Oil upon Pathogenic Bacteria - Asriani .; Betty Sri Laksmi; Sedernawati .; Idwan Sudirman (Jurnal Teknologi dan Industri Pangan, 2007)
Antibacterial mechanism of mixture between metabolites Lb.plantarum klik and monoacylglycerol coconut oil was found through analysis of the MIC levels. The level of 1 and 2 MIC can increase the leakages of the gram positif bacterial sell (L.monocytogenes and B.cereus) and that of the gram negative bacteria (S.typhimurium). The leackages of cell was measured by spectrofotometer and represented increasing of the absorbance of the protein nucleic acid . The absorbance of metal ion was evaluated using a AASS (measured by Atomic Absorption Spectrophotometer) and it indicated that the absorbance increased of 40.2% and 22.1% for Ca 2+ and K+ respectively. Observation of cell damage on L. monoctogenes and S. tyhimurium using SEM (scanning Electron Microscopy) resulted in morphological damage on both MIC 1 and 2 in which MIC 2 was severly damage. Key word : antibacterial mechanism, monoacylglycerol coconut oil, minimum inhibitory concentration